2010
DOI: 10.1111/j.1399-3038.2009.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Cow’s milk allergy is associated with changes in urinary organic acid concentrations

Abstract: Cow's milk allergy (CMA) is the most common form of food allergy affecting 2.5% of children, but the diagnosis is often difficult. Both intestinal microbiota and barrier function seem to be disturbed in patients with food allergies, and administration of probiotics has been shown to normalize intestinal microbiota and alleviate symptoms. We hypothesized that the differences in intestinal metabolic activity and permeability could lead to detectable changes in the end-products of metabolism in patients with CMA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…16,24,26 In addition to GM modifications, CMA children were reported to have decreased total SCFAs 14,16 and altered amino acids and nucleotide levels. 14,23 These findings are consistent with a recent review on the metabolic changes in children with IgE-mediated food allergies, 41 and these metabolome changes appear to be restored with interventions. Increased SCFAs and balanced amino acids were reported after treatment with LGG or lactose-supplemented EHF.…”
Section: Discussion and Con Clus I Onsupporting
confidence: 88%
“…16,24,26 In addition to GM modifications, CMA children were reported to have decreased total SCFAs 14,16 and altered amino acids and nucleotide levels. 14,23 These findings are consistent with a recent review on the metabolic changes in children with IgE-mediated food allergies, 41 and these metabolome changes appear to be restored with interventions. Increased SCFAs and balanced amino acids were reported after treatment with LGG or lactose-supplemented EHF.…”
Section: Discussion and Con Clus I Onsupporting
confidence: 88%
“…CM avoidance resulted in an increase in the proportion of lactobacilli and in a decrease in the proportion of enterobacteria and bifidobacteria. In another study , infants with CM allergy showed a different urinary metabolic profile compared with infants without FA, which may reflect differences in intestinal microbiota. The concentrations of urinary organic acids did not significantly change after 4 weeks of administration of Lactobacillus rhamnosus compared with placebo.…”
Section: Food Allergymentioning
confidence: 93%
“…Early colonization of the infant's gut is thought to protect against the development of allergic disease. Studies have characterized the commensal flora of infants with and without FA and tested the manipulation of the gut microflora through the administration of pre-and/or probiotics (6)(7)(8). Thompson-Chagoyan et al (6) reported that CM-allergic infants had higher total bacteria and anaerobic counts and lower yeast counts than healthy infants.…”
Section: Epidemiologymentioning
confidence: 99%
“…Measurement of urinary metabolites was performed with gas chromatography/mass spectrometry (GC/MS) by US BioTek Laboratories (Seattle, WA) according to the company's published method [18]. The subjects were not allowed to eat or drink on the morning of the test day.…”
Section: Methodsmentioning
confidence: 99%